2020
DOI: 10.3390/agronomy11010043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Spraying Pressure of an Injector Asymmetric Double Nozzle with Variable Flow on Head Fungicide Coverage, Yield, Grain Quality, and Deoxynivalenol Content in Winter Wheat

Abstract: Spraying parameters are important factors when spraying wheat heads against fusarium head blight (FHB) to control the deoxynivalenol level in the grain and to obtain high and quality yields. In 2019 and 2020, field trials were conducted in order to establish the effect of the spraying pressure (2 bar, 4 bar, and 6 bar) of special nozzles with a variable flow rate Agrotop VR 1.5 on the head fungicide coverage, yield parameters, and the deoxynivalenol (DON) value in the grain. The coverage of the front and rear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…One of the most important methods of prevention is fungicide protection, whose effectiveness depends not only on the type of active substance of the preparation, but also on the correct execution of the spraying procedure. As reported by Vučajnk et al [42], nozzle pressure has a major impact on the effectiveness of the treatment performed. In their results, the authors found that the 1000-grain weight was higher at a spraying pressure of 6 bar than at 2 or 4 bar.…”
Section: Characteristics Of the Most Common Fungal Diseasesmentioning
confidence: 83%
“…One of the most important methods of prevention is fungicide protection, whose effectiveness depends not only on the type of active substance of the preparation, but also on the correct execution of the spraying procedure. As reported by Vučajnk et al [42], nozzle pressure has a major impact on the effectiveness of the treatment performed. In their results, the authors found that the 1000-grain weight was higher at a spraying pressure of 6 bar than at 2 or 4 bar.…”
Section: Characteristics Of the Most Common Fungal Diseasesmentioning
confidence: 83%